Simple and affordable soft brace application in dystrophic epidermolysis bullosa patients - Wu, Chong; Jiao, Xin-He (Frontiers in Surgery, 2024)
Dystrophic epidermolysis bullosa (DEB) is a hereditary disease characterized by increased fragility of the epidermis and mucosa and is accompanied by blister formation following minor trauma. Repeated injuries cause contracture and scar formation, which can further result in hand deformity, leading to a decline in hand ability and a lower quality of life. In this study, after the scar release of patients' hands, we developed a new and practical portable soft support, and evaluated its efficacy in delaying the scar contracture of hands after operation.According to the hand function scores, the patients were divided into two groups.Those with excellent and good grades were assigned to the open hand function group, and those with poor grades were allocated to the restricted hand function group. The primary conditions, the use of a postoperative soft brace, and some common factors in the two groups were compared to determine whether these parameters influence postoperative hand function.There were no significant differences in age, gender, body mass index, ADL assessment index, albumin concentration, hemoglobin concentration, fasting blood glucose level, prothrombin time, and activated partial thromboplastin time between the two groups (p>0.05). In contrast, there was a significant difference between the two groups in the use of soft braces following the operation (p<0.05). The odds ratio of patients fixed with a brace compared with patients not fixed with soft braces was 11.01.Soft brace is a critical factor impacting the hand function of patients with dystrophic epidermolysis bullosa after scar contracture release in both hands. Indeed, a hand brace worn after the operation can delay the recurrence of scar contracture in both hands and offer patients a longer time to use their hands effectively. In addition, by restoring the appearance of patients' hands and some hand functions, patients' mental state and quality of life have been greatly improved.